Chizmachilikni o‗qitishda zamonaviy pedagogik texnologiyalarni tatbiq etish vositalari - Esboganova, B (SCIENCE and SOCIETY, 2023)
The article describes a method for increasing the effectiveness of the lesson and the activity of students through the use of pedagogical technologies in teaching sketching in higher education.
Keywords: activity; spatial imagination; pedagogical technology; thinking; imagination; technology; skill; ability; competence; methodology